Elements of Effective e-Learning Design - Brown, Andrew R.; Voltz, Bradley D. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
Preparing and developing e-learning materials is a costly and time consuming enterprise. This paper highlights the elements of effective design that we consider assist in the development of high quality materials in a cost efficient way. We introduce six elements of design and discuss each in some detail. These elements focus on paying attention to the provision of a rich learning activity, situating this activity within an interesting story line, providing meaningful opportunities for student reflection and third party criticism, considering appropriate technologies for delivery, ensuring that the design is suitable for the context in which it will be used, and bearing in mind the personal, social, and environmental impact of the designed activities. Along the way, we describe how these design elements can be effectively utilized by contextualizing them with examples from an e-learning initiative.